Bridging The Gap: Enhancing the Pedagogical Competence of Teachers at School in the Outermost Area of Jakarta - Ruhimat, Mochammad Devi Cahya; Rahyasih, Yayah; Shodikin, Rifan (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
The development of Indonesian education policy of teacher standard competence, changes in national curriculum, and new learning paradigm have become a difficult challenge for Indonesian teachers who must develop their abilities so fast. The difficult challenges is also witnessed by teachers in the state Elementary and Junior High Schools 2 under one roof of Sabira Island, a school at the outermost area of Jakarta, Indonesia. This research aims to design, implement, and report on the pedagogical competence enhance. A case study model descriptive type with a qualitative approach is utilized, and was conducted over 45 days. The result is; Developing a design of teacher is constructed as a workshop for on-the-job training; The workshop was held on November 2023 for 14 teachers based on the design formulated; The evaluation by the Kirkpatrick model shows that the workshop's aim is achieved. This result is crucial as a new model about how to improve the pedagogical competence of teachers. The implication is the educational policymakers must give a great attention to developing teachers’ pedagogical competence in the age of Merdeka Belajar. Considering the National Indonesian Education Assessment in 2023, we recommend the teachers’ training in other areas to develop Indonesian teacher competence.